Virtual Communication: Muslim Foodgram Participation Culture - Afifatur Rohimah; Rahma Sugihartati; santi Isnaini; Lukman Hakim (Jurnal Komunikasi, 2021)
The rapid development of the digital age has led humans to adapt new habits in communication. Communication activities are even very easy to do through digital platforms such as Instagram social media. Virtual communication activities conducted through halal culinary content are considered capable of creating information exchange. It is this exchange of information that makes participation happen virtually. Participation can not be considered as an activity without meaning, but when participation is done repeatedly, then the participation activity becomes a form of culture that has a certain meaning and interest. This research reveals virtual communication conducted by Muslim Instagram users who are actively producing kulier (Muslim foodgram) content through halal culinary content. The virtual ethnographic method was used by researchers to examine Henry Jenkins' theory of participation culture combined with smith's concept of researcher meaning. Based on the results of the study conducted for approximately eight months, researchers obtained data that virtual communication activities conducted by Muslim foodgrams are divided into several forms of participation such as affiliation, expression, collaboration, and circulation. not only a form of participation, researchers found that participation activities carried out by Muslim foodgrams through virtual communication occur continuously to form a culture. Participation culture formed from virtual communication activities include participation based on appreciation, participation based on existence, participation based on pleasure. The establishment of a culture of participation in virtual communication turns out to contain several meanings such as reputational interests, self-image, awards, hobbies, to careers.Perkembangan era digital yang semakin pesat telah membawa manusia pada adaptasi kebiasaan baru dalam berkomunikasi. Aktifitas komunikasi bahkan dengan sangat mudah dilakukan melalui platfoam digital seperti media sosial Instagram. Aktifitas komunikasi virtual yang dilakukan melalui konten kuliner halal dianggap mampu menciptakan pertukaran informasi. Pertukaran informasi inilah yang membuat adanya partisipasi terjadi secara virtual. Partisipasi tidak bisa dianggap sebagai aktifitas tanpa makna, tapi ketika partisipasi dilakukan berulang kali, maka aktifitas partisipasi menjadi bentuk budaya yang memiliki makna dan kepentingan tertentu. Penelitian ini mengungkap komunikasi virtual yang dilakukan oleh para pengguna Instagram muslim yang aktif memproduksi konten kulier (foodgram muslim) melalui sebuah konten kuliner halal. Metode etnografi virtual digunakan peneliti untuk mengkaji teori budaya partisipasi Henry Jenkins yang dikombinasikan dengan konsep makna peneliti dari Smith. Berdasarkan hasil penelitian yang dilakukan selama kurang lebih delapan bulan, peneliti mendapatkan data bahwa aktifitas komunikasi virtual yang dilakukan oleh foodgram muslim terbagi menjadi beberapa bentuk partisipasi seperti affiliation, expression, collaboration, dan circulation. tidak hanya bentuk partisipasi, peneliti menemukan bahwa aktifitas partisipasi yang dilakukan oleh foodgram muslim melalui komunikasi virtual terjadi terus-menerus hingga membentuk budaya. Budaya partisipasi yang terbentuk dari aktifitas komunikasi virtual meliputi participation based on appreciation, participation based on existence, participation based on pleasure. Terbentuknya budaya partisipasi dalam komunikasi virtual ternyata mengandung beberapa makna seperti kepentingan reputasi, citra diri, penghargaan, hobi, hingga karir.